2021
DOI: 10.3920/jiff2020.0061
|View full text |Cite
|
Sign up to set email alerts
|

Welfare of farmed insects

Abstract: The recent interest in using insects as food and feed is based on their capacity to be a sustainable alternative to other protein sources. When farmed as mini livestock, the question is raised as to whether they are ‘sentient beings’ (self-conscious)? In researching this topic, the problem is that humans often expect animals to have the same subjective experience as we do (anthropomorphic) and consider themselves as the centre of the universe (anthropocentric). We discuss insects’ sentience by looking at their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…Recent studies on pain perception [ 70 ], cognitive abilities [ 71 ], and pessimistic bias [ 72 ] have identified a variety of sophisticated responses in insects. Therefore, in his recent review, van Huis has suggested considering them “precautionary as sentient beings” [ 73 ]. On the other hand, there is limited information on practical welfare requirements for farmed insects, which might differ from vertebrates due to the considerable evolutionary distance and variability between species [ 69 ].…”
Section: Insect Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on pain perception [ 70 ], cognitive abilities [ 71 ], and pessimistic bias [ 72 ] have identified a variety of sophisticated responses in insects. Therefore, in his recent review, van Huis has suggested considering them “precautionary as sentient beings” [ 73 ]. On the other hand, there is limited information on practical welfare requirements for farmed insects, which might differ from vertebrates due to the considerable evolutionary distance and variability between species [ 69 ].…”
Section: Insect Farmingmentioning
confidence: 99%
“…Different killing methods have recently been described, such as hot water, boiling vapor, freezing, and mincing [ 75 ]. Finally, insect farmers and veterinary authorities should be kept abreast of the latest science regarding the possible experiences of fear and distress in different species, and further research on this is needed [ 69 , 73 ].…”
Section: Insect Farmingmentioning
confidence: 99%
“…Finally, insects engage in social and sexual interactions, and may have specific requirements for these behaviours, such as particular light conditions. Surprisingly little is known about how to assess welfare of insects, in particular under mass-rearing conditions, and which parameters should be measured to assess their welfare (Van Huis, 2020b). Optimisation of mass-rearing conditions that safeguard insect health, welfare and quality requires a comprehensive assessment of various indicators, such as behaviour, longevity, disease or immune activation, productivity and physiology.…”
Section: Production Of Insectsmentioning
confidence: 99%
“…Animal welfare is a critical issue for the insects as food and feed sector (Van Huis, 2021). The central question in this debate is whether insects are 'sentient beings' .…”
Section: Insect Welfarementioning
confidence: 99%